Composite positive electrode material, positive plate and secondary battery
By using the coating technology of carbon-coated sodium phosphate phosphate material on the sodium ferric sulfate positive electrode material, the carbon-coated layer is formed, which solves the problems of low capacity and poor high-temperature circulation performance of sodium ferric sulfate positive electrode material, and achieves high efficiency The energy density and cycle stability are improved.
Patent Information
- Application Number
- CN202411048119.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-01
- Publication Date
- 2024-12-13
AI Technical Summary
The existing sodium ferrosulfate positive electrode material has low gauge capacity, poor high-temperature cycling performance, and the existing carbon coating technology is difficult to achieve good coating properties, so it is impossible to effectively improve the performance of sodium ferrosulfate positive electrode material.
The composite positive electrode material is adopted, including composite sodium ferrosulfate material and carbon-coated sodium phosphate phosphate material, and the composite sodium ferrosulfate material is coated by carbon-coated sodium phosphate phosphate material to form a carbon coating on the surface of sodium ferrosulfate layer, improve conductivity and capacity.
It significantly improves the high temperature resistance and capacity of the composite positive electrode material, improves the energy density and cycle stability of the secondary battery, and extends the life.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a composite positive electrode material, a positive electrode sheet and a secondary battery. Background Art
[0002] With the continuous advancement of sodium-ion battery technology, the improvement of energy density has led to a significant increase in the demand for sodium-ion batteries in the fields of new energy vehicles and energy storage power sources. Among them, sodium iron sulfate positive electrode materials have long life, simple preparation process, low raw material cost, and high voltage platform. They have the characteristics of fast charging and discharging, low temperature resistance and safe use. They have gradually become the first choice for positive electrode materials in sodium-ion batteries. However, sodium iron sulfate has a low gram capacity and poor high-temperature cycle, which limits the application of sodium iron sulfate positive electrode materials in sodium-ion batteries. In addition, some existing sodium iron sulfate positive electrode materials generally add carbon materials to improve conductivity during the formation process, but the sintering temperature is low, and a good carbon coating cannot be formed on the surface of sodium iron sulfate. Properties such as conductivity and gram capacity are still difficult to meet the requirements of sodium-ion batteries. Summary of the invention
[0003] In view of the problems existing in the above-mentioned prior art, the present application provides a composite positive electrode material, a positive electrode sheet and a secondary battery, and the technical solution is as follows: On the one hand, the present application provides a composite positive electrode material, including a composite sodium iron sulfate material and a carbon-coated sodium iron phosphate pyrophosphate material, wherein the composite sodium iron sulfate material includes a first carbon material and sodium iron sulfate, and the first carbon material and the sodium iron sulfate are blended; the carbon-coated sodium iron phosphate pyrophosphate material includes a second carbon material and sodium iron phosphate pyrophosphate, and the second carbon material coats the sodium iron phosphate pyrophosphate; the carbon-coated sodium iron phosphate pyrophosphate material coats the composite sodium iron sulfate material.
[0004] Furthermore, the mass of each component in the composite positive electrode material satisfies at least one of the following characteristics: The mass ratio between the composite sodium iron sulfate material and the carbon-coated sodium iron phosphate pyrophosphate material is 1:1 to 5:1; The mass percentage of the composite sodium iron sulfate material in the composite positive electrode material is 40% to 95%; The mass percentage of the carbon-coated sodium iron phosphate pyrophosphate material in the composite positive electrode material is 5% to 60%.
[0005] Furthermore, the molecular formula of sodium ferric sulfate in the composite sodium ferric sulfate material is Na m Fe(SO4) n , where m+2=2n, 0.8≤m≤3.2, 1.3≤n≤2.7.
[0006] Furthermore, the particle size of the composite positive electrode material satisfies at least one of the following characteristics: The particle size of the composite sodium iron sulfate material is greater than the particle size of the carbon-coated sodium iron phosphate pyrophosphate material; The median particle size of the composite sodium iron sulfate material is smaller than the first preset particle size, and the first preset particle size is 3 μm to 7 μm; The median particle size of the carbon-coated sodium iron phosphate pyrophosphate material is smaller than the second preset particle size, and the second preset particle size is 1 μm to 2.5 μm.
[0007] Furthermore, the surface area of the composite positive electrode material satisfies at least one of the following characteristics: The total surface area of the sodium iron sulfate in the composite sodium iron sulfate material is 15% to 50% of the total surface area of the carbon-coated sodium iron phosphate pyrophosphate material; The specific surface area of sodium iron sulfate in the composite sodium iron sulfate material is 2m 2 / g~5m 2 / g; The specific surface area of the first carbon material in the composite sodium iron sulfate material is 50 m 2 / g~350m 2 / g; The specific surface area of the carbon-coated sodium iron phosphate pyrophosphate material is 12 m 2 / g~25m 2 / g.
[0008] Furthermore, the first carbon material and the second carbon material satisfy at least one of the following characteristics: The mass percentage of the first carbon material in the composite sodium iron sulfate material is 2% to 10%; The mass percentage of the second carbon material in the carbon-coated sodium iron phosphate pyrophosphate material is 1% to 5%.
[0009] Furthermore, the mass ratio of the composite sodium iron sulfate material and the carbon-coated sodium iron phosphate pyrophosphate material satisfies the following formula: 0.15≤((x*z)*A1) / (y*A2)≤0.5; Among them, x is the mass proportion of the composite sodium iron sulfate material in the composite positive electrode material, y is the mass proportion of the carbon-coated sodium iron phosphate pyrophosphate material in the composite positive electrode material; z is the mass proportion of the sodium iron sulfate in the composite sodium iron sulfate material, A1 is the specific surface area of the sodium iron sulfate in the composite sodium iron sulfate material; A2 is the specific surface area of the carbon-coated sodium iron phosphate pyrophosphate material.
[0010] Furthermore, the composite positive electrode material further includes at least one of a conductive agent and a binder, and the composite positive electrode material satisfies at least one of the following characteristics: The conductive agent includes at least one of conductive carbon black, acetylene black, graphite, graphene, carbon nanotubes and carbon nanofibers; The mass percentage of the conductive agent in the composite positive electrode material is 0.1% to 10%; The binder comprises at least one of polyvinylidene fluoride, modified polyvinylidene fluoride, polyvinylidene chloride, modified polyvinylidene chloride, polyvinylidene fluoride copolymer, polyvinylidene chloride copolymer, polymethyl methacrylate and styrene-butadiene rubber; The mass percentage of the binder in the composite positive electrode material is 0.1% to 10%.
[0011] Furthermore, the compaction density of the composite positive electrode material is 1.9 g / cm 3 ~2.4g / cm 3 .
[0012] On the other hand, the present application also provides a positive electrode sheet, comprising a current collector and a composite positive electrode material as described in any one of the above items, wherein the composite positive electrode material is located on the surface of the current collector.
[0013] On the other hand, the present application also provides a secondary battery, comprising the composite positive electrode material as described in any one of the above items, or comprising the positive electrode sheet as described above.
[0014] On the other hand, the present application also provides an electronic device, comprising the secondary battery as described above.
[0015] Implementing this application has the following beneficial effects: 1. In the composite positive electrode material of the present application, the carbon-coated sodium iron phosphate pyrophosphate material is coated on the composite sodium iron sulfate material, which can greatly improve the high temperature resistance of the composite positive electrode material, and is beneficial to improving the high temperature cycle stability of the positive electrode sheet and the secondary battery having the composite positive electrode material; and the second carbon material in the carbon-coated sodium iron phosphate pyrophosphate material forms a good carbon coating on the sodium iron phosphate pyrophosphate, and through the coating effect of the carbon-coated sodium iron phosphate pyrophosphate material on the composite sodium iron sulfate material as a whole, the second carbon material can be coated on the composite sodium iron sulfate material together, which is equivalent to forming a layer of carbon coating on the surface of sodium iron sulfate, and the carbon coating has good coating properties, which can greatly improve the conductivity of sodium iron sulfate, and is more conducive to the release of sodium ions in sodium iron sulfate. Compared with a simple composite sodium iron sulfate material or a simple carbon-coated sodium iron phosphate pyrophosphate material, the overall gram capacity of the composite positive electrode material can be effectively improved, and the energy density of the positive electrode sheet and the secondary battery having the composite positive electrode material can be improved, so as to achieve a synergistic improvement in reversible gram capacity, energy density and cycle stability.
[0016] 2. In the composite positive electrode material of the present application, the particle size of the carbon-coated sodium iron phosphate pyrophosphate material is smaller than that of the composite sodium ferric sulfate material, while the specific surface area of the carbon-coated sodium iron phosphate pyrophosphate material is greater than the specific surface area of sodium ferric sulfate, and the total surface area of the carbon-coated sodium iron phosphate pyrophosphate material is also greater than the total surface area of sodium ferric sulfate, so that the carbon-coated sodium iron phosphate pyrophosphate material can be stably and reliably coated on the composite sodium ferric sulfate material, thereby improving the coating effectiveness, coating stability and coating accuracy, and thus improving the molding accuracy and yield of the composite positive electrode material, which is beneficial to improving the performance stability of the positive electrode sheet and secondary battery having the composite positive electrode material, and is beneficial to extending the life. DETAILED DESCRIPTION
[0017] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments, and therefore cannot be understood as limiting the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0018] It should be noted that in the description of the present application, for the following defined terms, unless a different definition is given in the claims or elsewhere in this specification, these definitions should be applied. All numerical values, whether or not explicitly indicated, are defined herein as being modified by the term "about". The term "about" generally refers to a numerical range that a person of ordinary skill in the art would consider to be equivalent to the stated value to produce substantially the same properties, functions, results, etc. A numerical range indicated by a low value and a high value is defined to include all numerical values included in the numerical range and all subranges included in the numerical range.
[0019] It should be noted that the terms "first", "second" etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequential order. It should be understood that the objects used in this way can be interchanged in appropriate circumstances, so that the embodiments of the present application can be implemented in the order except for the following description. In addition, the terms "comprise" and "have" and any of their variations are intended to cover non-exclusive inclusions, for example, the process, method, system, product comprising a series of steps or units need not be limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, or products.
[0020] The existing sodium ferric sulfate positive electrode material has low gram capacity and poor high-temperature cycle performance, and it is difficult to achieve good coating by coating with carbon materials, and the performance of the sodium ferric sulfate positive electrode material cannot be effectively improved. In order to solve at least one of the above-mentioned problems faced by the sodium ferric sulfate positive electrode material, the embodiment of the present application provides a composite positive electrode material, a positive electrode sheet and a secondary battery, the composite positive electrode material includes a composite sodium ferric sulfate material and a carbon-coated sodium ferric phosphate pyrophosphate material, the composite sodium ferric sulfate material includes a first carbon material and sodium ferric sulfate, and the first carbon material and the sodium ferric sulfate are blended; the carbon-coated sodium ferric phosphate pyrophosphate material includes a second carbon material and sodium ferric phosphate pyrophosphate, and the second carbon material coats the sodium ferric phosphate pyrophosphate; the carbon-coated sodium ferric phosphate pyrophosphate material coats the composite sodium ferric sulfate material, which can greatly improve the high temperature resistance of the composite registration material, thereby improving the high temperature cycle stability of the positive electrode sheet and the secondary battery having the composite positive electrode material, and in the process of the carbon-coated sodium ferric phosphate pyrophosphate material being coated on the composite sodium ferric sulfate material as a whole, the second carbon material can be The coated composite sodium ferric sulfate material, that is, the coating effect of the carbon-coated sodium ferric phosphate pyrophosphate material on the composite sodium ferric sulfate material is equivalent to forming a carbon layer on the surface of the composite sodium ferric sulfate material; it should be noted that in the composite sodium ferric sulfate material, part of the first carbon material is located inside the sodium ferric sulfate, and the other part of the first carbon material is located on the surface of the sodium ferric sulfate, but the first carbon material and the sodium ferric sulfate are in a mixed state and it is difficult to achieve good coating of the sodium ferric sulfate by the carbon layer, then by coating the carbon-coated sodium ferric phosphate pyrophosphate material having the second carbon material on the composite sodium ferric sulfate material, the purpose of forming a carbon layer on the surface of the sodium ferric sulfate is indirectly achieved, the conductivity of the composite sodium ferric sulfate material is greatly improved, and it is also beneficial to the release of sodium ions in the composite sodium ferric sulfate material. Compared with a single sodium ferric sulfate system and a single sodium ferric phosphate pyrophosphate system, the gram capacity of the composite positive electrode material has been effectively improved, which is beneficial to improve the reversible gram capacity, energy density, room temperature cycle performance and high temperature cycle performance of the positive electrode sheet, battery cell and secondary battery having the composite positive electrode material.
[0021] Specifically, in some exemplary embodiments, the mass ratio between the composite sodium ferric sulfate material and the carbon-coated sodium ferric phosphate pyrophosphate material is 1:1 to 5:1; it can be understood that the mass ratio between the composite sodium ferric sulfate material and the carbon-coated sodium ferric phosphate pyrophosphate material can be any point value between 1:1 and 5:1; illustratively, the mass ratio between the composite sodium ferric sulfate material and the carbon-coated sodium ferric phosphate pyrophosphate material can be 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 4:1, 5:1, etc.; in this way, the high temperature resistance of the composite positive electrode material can be effectively improved, which can be better than the single composite sodium ferric sulfate material and the single carbon-coated sodium ferric phosphate pyrophosphate material, thereby improving the high temperature cycle stability of the positive electrode sheet and the secondary battery as a whole with the composite positive electrode material, and achieving good coating of the composite sodium ferric sulfate material, effectively improving the conductivity of the composite positive electrode material, facilitating the escape of sodium ions, and improving the gram capacity of the composite positive electrode material, as well as the energy density of the secondary battery with the composite positive electrode material.
[0022] Specifically, in some exemplary embodiments, the mass percentage of the composite sodium ferric sulfate material in the composite positive electrode material is 40% to 95%; it can be understood that the mass percentage of the composite sodium ferric sulfate material in the composite positive electrode material can be any point value between 40% and 95%; illustratively, the mass percentage of the composite sodium ferric sulfate material in the composite positive electrode material can be 40%, 45%, 50%, 55%, 60%, 70%, 80%, 90%, 95%, etc.
[0023] Specifically, in some exemplary embodiments, the mass percentage of the carbon-coated sodium iron phosphate pyrophosphate material in the composite positive electrode material is 5% to 60%; it can be understood that the mass percentage of the carbon-coated sodium iron phosphate pyrophosphate material in the composite positive electrode material can be any point value between 5% and 60%; exemplarily, the mass percentage of the carbon-coated sodium iron phosphate pyrophosphate material in the composite positive electrode material can be 5%, 10%, 15%, 25%, 30%, 50%, 55%, 60%, etc.
[0024] In this way, the carbon-coated sodium iron phosphate pyrophosphate material can effectively coat the composite sodium iron sulfate material, while improving the high temperature resistance of the composite positive electrode material, effectively improving the conductivity and gram capacity of the composite positive electrode material, thereby improving the energy density of the positive electrode sheet and the secondary battery with the composite positive electrode material, and extending the life of the positive electrode sheet and the secondary battery.
[0025] Specifically, in this embodiment, the molecular formula of sodium iron sulfate in the composite sodium iron sulfate material is Na m Fe(SO4) n, wherein m+2=2n, 0.8≤m≤3.2, 1.3≤n≤2.7; in the present embodiment, the molecular formula of sodium ferric phosphate pyrophosphate in the carbon-coated sodium ferric phosphate pyrophosphate material is Na4Fe3(PO4)2(P2O7); the sodium ferric sulfate has a high voltage platform and low raw material cost, while the sodium ferric phosphate pyrophosphate has a high gram capacity, excellent cycle performance, and good high-temperature performance. The preparation process of the composite sodium ferric sulfate material based on the sodium ferric sulfate and the preparation process of the carbon-coated sodium ferric phosphate pyrophosphate material based on the sodium ferric phosphate pyrophosphate are both relatively simple, which is beneficial to improving the electrochemical properties of the composite sodium ferric sulfate material and the carbon-coated sodium ferric phosphate pyrophosphate material, and also enables the composite positive electrode material having the composite sodium ferric sulfate material and the carbon-coated sodium ferric phosphate pyrophosphate material to be quickly charged and discharged and resistant to low temperatures, which is beneficial to improving the life of the composite positive electrode material and has high safety in use.
[0026] Specifically, the particle size of the composite sodium iron sulfate material is larger than that of the carbon-coated sodium iron phosphate pyrophosphate material. In the process of preparing the composite positive electrode material, the carbon-coated sodium iron phosphate pyrophosphate material can be stably and effectively coated on the composite sodium iron sulfate material. The coating effect of the carbon-coated sodium iron phosphate material on the composite sodium iron sulfate material indirectly realizes the effective coating of the composite sodium iron sulfate material by the second carbon material, which is equivalent to forming a good carbon coating layer on the surface of sodium iron sulfate, greatly improving the overall conductivity of the composite positive electrode material, and is also beneficial to the release of sodium ions in sodium iron sulfate, which is beneficial to improving the overall gram capacity of the composite positive electrode material and the energy density of the positive electrode sheet and secondary battery having the composite positive electrode material.
[0027] Specifically, in some exemplary embodiments, the median particle size D50 of the composite sodium ferric sulfate material is smaller than the first preset particle size, the first preset particle size is 3 μm to 7 μm, and the median particle size refers to the particle diameter size when the cumulative particle size distribution reaches 50%; it can be understood that the first preset particle size can be any point value between 3 μm and 7 μm; exemplarily, the first preset particle size can be 3 μm, 3.5 μm, 4 μm, 5 μm, 5.5 μm, 6 μm, 7 μm, etc.; in some preferred embodiments, the first preset particle size can be 5 μm, that is, the median particle size D50 of the composite sodium ferric sulfate material is less than 5 μm.
[0028] Specifically, in some exemplary embodiments, the median particle size D50 of the carbon-coated sodium iron phosphate pyrophosphate material is smaller than the second preset particle size, and the second preset particle size is 1 μm to 2.5 μm; it can be understood that the second preset particle size can be any point value between 1 μm and 2.5 μm; exemplarily, the second preset particle size can be 1 μm, 1.5 μm, 1.8 μm, 2 μm, 2.3 μm, 2.5 μm, etc.; in some preferred embodiments, the second preset particle size can be 1.5 μm, that is, the median particle size D50 of the carbon-coated sodium iron phosphate pyrophosphate material is less than 1.5 μm.
[0029] In this way, the median particle size of the composite sodium ferric sulfate material is relatively large, while the median particle size of the carbon-coated sodium ferric phosphate pyrophosphate material is relatively small. The particle size of the composite sodium ferric sulfate material is generally larger than that of the carbon-coated sodium ferric phosphate pyrophosphate material. In the process of mixing the two to form a composite positive electrode material, the carbon-coated sodium ferric phosphate pyrophosphate material with a smaller particle size can be effectively coated on the composite sodium ferric sulfate material with a relatively larger particle size, and the coating effectiveness and coating stability are good, so that the structural stability, conductive properties, reversible gram capacity, room temperature cycle performance and high temperature cycle performance of the composite positive electrode material can be effectively and synergistically improved.
[0030] Specifically, in some exemplary embodiments, the D10 of the composite sodium ferric sulfate material is less than 2 μm, and the Dmax is less than 15 μm, wherein D10 refers to the diameter of the particles when the cumulative particle size distribution reaches 10%, and Dmax refers to the maximum particle size in the particle distribution; it can be understood that the D10 of the composite sodium ferric sulfate material can be any point value less than 2 μm, and Dmax can be any point value less than 15 μm, which are not enumerated here.
[0031] Specifically, in some exemplary embodiments, the D10 of the carbon-coated sodium iron phosphate pyrophosphate material is less than 0.5 μm, and the Dmax is less than 3 μm; it is understandable that the D10 of the carbon-coated sodium iron phosphate pyrophosphate material can be any point value less than 0.5 μm, and the Dmax can be any point value less than 3 μm, which are not enumerated here.
[0032] In this way, the particle size of the composite sodium ferric sulfate material is generally larger than that of the carbon-coated sodium ferric phosphate pyrophosphate material in each particle size range. In the process of mixing the two to form a composite positive electrode material, the particle size of the composite sodium ferric sulfate material is within the corresponding particle size range and the particle size of the carbon-coated sodium ferric phosphate pyrophosphate material is within the corresponding particle size range. Only in this way can the carbon-coated sodium ferric phosphate pyrophosphate material be stably and effectively coated on the composite sodium ferric sulfate material during the preparation of the composite positive electrode material, thereby improving the yield of the preparation of the composite positive electrode material and its morphology accuracy, and also improving the coating property of the second carbon material on sodium ferric sulfate in the composite positive electrode material, thereby greatly improving the conductivity, reversible gram capacity, room temperature cycle performance and high temperature cycle performance of the composite positive electrode material and a secondary battery having the composite positive electrode material.
[0033] Specifically, the total surface area of sodium iron sulfate in the composite sodium iron sulfate material is less than the total surface area of the carbon-coated sodium iron phosphate pyrophosphate material; in some exemplary embodiments, the total surface area of sodium iron sulfate in the composite sodium iron sulfate material is 15% to 50% of the total surface area of the carbon-coated sodium iron phosphate pyrophosphate material; it can be understood that the total surface area of sodium iron sulfate in the composite sodium iron sulfate material can be any point value between 15% and 50% of the total surface area of the carbon-coated sodium iron phosphate pyrophosphate material; illustratively, the total surface area of sodium iron sulfate in the composite sodium iron sulfate material can be the total surface area of the carbon-coated sodium iron phosphate pyrophosphate material. In this way, the coating of the carbon-coated sodium iron phosphate pyrophosphate material on the surface of the composite sodium iron sulfate material can be promoted, and the coating effectiveness, coating stability and coating reliability of the second carbon material with the carbon-coated sodium iron phosphate pyrophosphate material on the surface of the composite sodium iron sulfate material can be greatly improved, the conductivity of sodium iron sulfate can be improved, and it is beneficial to the escape of sodium ions, thereby improving the overall gram capacity of the composite positive electrode material, and further improving the energy density, reversible gram capacity and high temperature cycle stability of the positive electrode sheet and secondary battery having the composite positive electrode material.
[0034] Specifically, the mass ratio of the composite sodium iron sulfate material and the carbon-coated sodium iron phosphate pyrophosphate material satisfies the following formula: 0.15≤((x*z)*A1) / (y*A2)≤0.5; Among them, x is the mass proportion of the composite sodium iron sulfate material in the composite positive electrode material, y is the mass proportion of the carbon-coated sodium iron phosphate pyrophosphate material in the composite positive electrode material; z is the mass proportion of sodium iron sulfate in the composite sodium iron sulfate material, A1 is the specific surface area of sodium iron sulfate in the composite sodium iron sulfate material; A2 is the specific surface area of the carbon-coated sodium iron phosphate pyrophosphate material.
[0035] When the mass ratio of the composite sodium ferric sulfate material and the carbon-coated sodium ferric phosphate pyrophosphate material satisfies 0.15≤((x*z)*A1) / (y*A2)≤0.5, compared with the single composite sodium ferric sulfate material and the single carbon-coated sodium ferric phosphate pyrophosphate material, the high temperature resistance of the composite positive electrode material can be effectively improved, thereby improving the high temperature cycle stability of the positive electrode sheet and the secondary battery as a whole with the composite positive electrode material, and avoiding the excessive proportion of the carbon-coated sodium ferric phosphate pyrophosphate material to affect the initial efficiency of the secondary battery. In addition, the carbon-coated sodium ferric phosphate pyrophosphate material can also achieve good coating of the composite sodium ferric sulfate material, effectively improving the conductivity of the composite positive electrode material, facilitating the escape of sodium ions, and increasing the gram capacity of the composite positive electrode material, as well as the energy density of the secondary battery with the composite positive electrode material.
[0036] Specifically, the specific surface area of sodium ferric sulfate in the composite sodium ferric sulfate material is smaller than that of the carbon-coated sodium ferric phosphate pyrophosphate material, so that the carbon-coated sodium ferric phosphate pyrophosphate material has stronger adsorption than the composite sodium ferric sulfate material and better cohesion. In the process of preparing the composite positive electrode material, it is beneficial to promote the carbon-coated sodium ferric phosphate pyrophosphate material to be stably and effectively coated on the composite sodium ferric sulfate material, so as to improve the effectiveness, reliability and stability of indirectly forming a coated carbon layer on the composite sodium ferric sulfate material. The preparation yield is high and the morphology accuracy of the composite positive electrode material is high, which is beneficial to synergistically improve the high-temperature cycle stability, gram capacity and energy density of the composite positive electrode material.
[0037] Specifically, in some exemplary embodiments, the specific surface area of the first carbon material in the composite sodium iron sulfate material is 50 m 2 / g~350m 2 / g; It can be understood that the specific surface area of the first carbon material in the composite sodium iron sulfate material can be 50m 2 / g~350m 2 / g; For example, the specific surface area of the first carbon material in the composite sodium iron sulfate material can be 50m 2 / g,100m 2 / g,150m 2 / g,200m 2 / g,250m 2 / g,300m 2 / g,350m 2 / g, etc.; in this way, it is beneficial for the first carbon material and sodium ferric sulfate to form a uniform and stable blending state, thereby improving the conductive properties of sodium ferric sulfate, and is also beneficial for assisting the carbon-coated sodium ferric phosphate pyrophosphate material to coat the composite sodium ferric sulfate material during the mixing process of the composite sodium ferric sulfate material and the carbon-coated sodium ferric phosphate pyrophosphate material, thereby improving the coating effectiveness and coating stability, and further promoting the synergistic improvement of reversible gram capacity, energy density and cycle stability.
[0038] Specifically, in some exemplary embodiments, the specific surface area of sodium iron sulfate in the composite sodium iron sulfate material is 2 m 2 / g~5m 2 / g; It can be understood that the specific surface area of sodium iron sulfate in the composite sodium iron sulfate material can be 2m 2 / g~5m 2 / g; For example, the specific surface area of sodium iron sulfate in the composite sodium iron sulfate material can be 2m 2 / g, 2.5m 2 / g,3m 2 / g,3.5m 2 / g,4m 2 / g,4.5m 2 / g,5m 2 / g, etc.
[0039] Specifically, in some exemplary embodiments, the specific surface area of the carbon-coated sodium iron phosphate pyrophosphate material is 12 m 2 / g~25m 2 / g; It can be understood that the specific surface area of the carbon-coated sodium iron phosphate pyrophosphate material can be 12m 2 / g~25m 2 / g; For example, the specific surface area of the carbon-coated sodium iron phosphate pyrophosphate material can be 12 m 2 / g,15m 2 / g,18m 2 / g,20m 2 / g,22m 2 / g,25m 2 / g, etc.
[0040] In this way, the specific surface area of sodium ferric sulfate is smaller than that of the carbon-coated sodium ferric phosphate pyrophosphate material, and the specific surface area of the carbon-coated sodium ferric phosphate pyrophosphate material is relatively large. The carbon-coated sodium ferric phosphate pyrophosphate material has high surface energy, large surface activity, and is easy to agglomerate, which is beneficial to promote the coating of the composite sodium ferric sulfate material by the carbon-coated sodium ferric phosphate pyrophosphate material, improve the coating effectiveness, coating accuracy, coating reliability and coating stability, and thus improve the high temperature resistance and gram capacity of the composite positive electrode material, which is beneficial to improve the high temperature resistance and energy density of the positive electrode sheet and secondary battery having the composite positive electrode material, and is also beneficial to prolonging the life of the positive electrode sheet and the secondary battery. In addition, while improving the above-mentioned performance, the room temperature cycle stability of the positive electrode sheet and the secondary battery can also be simultaneously improved to a certain extent.
[0041] In some exemplary embodiments, the first carbon material is a conductive carbon material, including at least one of carbon nanotubes (CNTs) and graphene; exemplarily, in some embodiments, the first carbon material is a carbon nanotube, the diameter of the carbon nanotube is 5nm to 12nm, and the aspect ratio is 120 to 150. The carbon nanotube can be uniformly blended with sodium ferric sulfate, to a certain extent improve the conductivity of the composite sodium ferric sulfate material, and facilitate the release of sodium ions, thereby improving the gram capacity of the composite sodium ferric sulfate material and the composite positive electrode material.
[0042] Specifically, in some exemplary embodiments, the mass percentage of the first carbon material in the composite sodium ferric sulfate material is 2% to 10%; it can be understood that the mass percentage of the first carbon material in the composite sodium ferric sulfate material can be any point value between 2% and 10%; exemplarily, the mass percentage of the first carbon material in the composite sodium ferric sulfate material can be 2%, 2.5%, 3%, 5%, 7%, 9%, 10%, etc.; by blending the first carbon material with sodium ferric sulfate, although good surface coating cannot be achieved, the first carbon material is partially distributed inside the composite sodium ferric sulfate material and partially distributed on the surface of the composite sodium ferric sulfate material, which can also improve the conductivity of the composite sodium ferric sulfate material to a certain extent. In the subsequent process of forming a composite positive electrode material, it is also beneficial to further improve the conductivity of the composite positive electrode material, increase the escape path of sodium ions in sodium ferric sulfate, facilitate the escape of sodium ions, thereby improving the overall gram capacity of the composite positive electrode material and the energy density of the positive electrode sheet and secondary battery having the composite positive electrode material.
[0043] In some exemplary embodiments, the second carbon material is a carbon coating layer formed on the surface of sodium ferric pyrophosphate after adding a carbon source to sodium ferric pyrophosphate and carbonizing it at high temperature; exemplarily, the carbon source can be a polymer material, and the polymer material can include at least one of chitosan, polyethylene polyamine, and polyacrylamide, which can stably form a carbon coating layer after high-temperature carbonization, and has good coating properties for sodium ferric pyrophosphate, which is beneficial to improving the overall gram capacity of the subsequent composite positive electrode material; it should be noted that the above-mentioned polymer materials are only examples, and the present invention does not make specific limitations on this. As long as the carbon source can form a good carbon coating on the surface of sodium ferric pyrophosphate, it can be within the protection scope of the present invention.
[0044] Specifically, in some exemplary embodiments, the mass percentage of the second carbon material in the carbon-coated sodium iron phosphate pyrophosphate material is 1% to 5%; it can be understood that the mass percentage of the second carbon material in the carbon-coated sodium iron phosphate pyrophosphate material can be any point value between 1% and 5%; exemplarily, the mass percentage of the second carbon material in the carbon-coated sodium iron phosphate pyrophosphate material can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 5%, etc.; in this way, a good carbon coating can be formed on the surface of the sodium phosphate pyrophosphate, which is beneficial to indirectly form a good carbon coating on the composite sodium iron sulfate material through the overall coating effect of the carbon-coated sodium iron phosphate pyrophosphate material on the composite sodium iron sulfate material in the process of forming the composite positive electrode material, thereby improving the conductivity of the composite positive electrode material, facilitating the escape of sodium ions, and helping to improve the overall gram capacity of the composite positive electrode material, and further improving the energy density, cycle performance and high temperature resistance of the positive electrode sheet and secondary battery having the composite positive electrode material.
[0045] Specifically, the composite positive electrode material also includes at least one of a conductive agent and a binder, wherein the conductive agent can reduce the contact resistance between the composite positive electrode material and the current collector in the positive electrode sheet, improve the ionic conductivity of the composite positive electrode material, can greatly improve the charge and discharge efficiency of the composite positive electrode material, and is also beneficial to improving the processability of the composite positive electrode material, and is beneficial to extending the life of the composite positive electrode material and the positive electrode sheet and secondary battery having the composite positive electrode material; the binder can enhance the contact effectiveness between the composite sodium ferric sulfate material and the carbon-coated sodium ferric phosphate pyrophosphate material and the conductive agent, and can also enhance the contact benignity between the composite positive electrode material and the current collector during the application of the composite positive electrode material in the positive electrode sheet, which is beneficial to improving the bonding of the composite positive electrode material, improving the bonding reliability and bonding stability between the composite positive electrode material and the current collector, further improving the structural stability and life of the positive electrode sheet having the composite positive electrode material, and is beneficial to extending the service life of the positive electrode sheet and the secondary battery having the composite positive electrode material; preferably, in some embodiments, the composite positive electrode material includes a conductive agent and a binder.
[0046] Specifically, in some exemplary embodiments, the conductive agent includes at least one of conductive carbon black, acetylene black, graphite, graphene, carbon nanotubes and carbon nanofibers, which has good conductivity and is beneficial to improving ionic conductivity.
[0047] Specifically, in some exemplary embodiments, the mass percentage of the conductive agent in the composite positive electrode material is 0.1% to 10%; it can be understood that the mass percentage of the conductive agent in the composite positive electrode material can be any point value between 0.1% and 10%; illustratively, the mass percentage of the conductive agent in the composite positive electrode material can be 0.1%, 0.5%, 1%, 2.5%, 5%, 7.5%, 10%, etc.; in this way, it is convenient for sodium ions in the composite positive electrode material to escape, greatly improving the ionic conductivity, and also beneficial to improving the processability of the composite positive electrode material, which is beneficial to the application of the composite positive electrode material in the secondary battery. The electrode liquid infiltrates the composite positive electrode material, further improving the charge and discharge performance.
[0048] Specifically, in some exemplary embodiments, the binder includes at least one of polyvinylidene fluoride, modified polyvinylidene fluoride, polyvinylidene chloride, modified polyvinylidene chloride, polyvinylidene fluoride copolymer, polyvinylidene chloride copolymer, polymethyl methacrylate and styrene-butadiene rubber, and has good adhesion, which is beneficial to improving the adhesion reliability and coating reliability of the carbon-coated sodium ferric phosphate pyrophosphate material on the composite sodium ferric sulfate material, and improving the cycle performance and life of the positive electrode sheet and secondary battery having the composite positive electrode material.
[0049] Specifically, in some exemplary embodiments, the mass percentage of the binder in the composite positive electrode material is 0.1% to 10%; it can be understood that the mass percentage of the binder in the composite positive electrode material can be any point value in the range of 0.1% to 10%; illustratively, the mass percentage of the binder in the composite positive electrode material can be 0.1%, 0.5%, 1%, 2.5%, 5%, 7.5%, 10%, etc.; in this way, while avoiding affecting the gram capacity of the composite positive electrode material, the bonding reliability and coating reliability of the carbon-coated phosphate iron pyrophosphate material on the composite sodium ferric sulfate material in the composite positive electrode material can be greatly improved, and it is also beneficial to reduce the subsequent bonding reliability between the composite positive electrode material and the current collector, while improving the energy density of the positive electrode sheet and the secondary battery having the composite positive electrode material, greatly improving its structural stability and durability, and extending its service life.
[0050] Specifically, in some exemplary embodiments, the composite cathode material is a cathode film layer located on the surface of the current collector, and the compaction density of the composite cathode material is 1.9 g / cm 3 ~2.4g / cm 3 It can be understood that the compaction density of the composite cathode material can be 1.9 g / cm 3 ~2.4g / cm 3 For example, the compaction density of the composite cathode material can be 1.9 g / cm 3 , 2.0g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 , 2.35g / cm 3 , 2.4g / cm 3 etc.; within this compaction density range, it is beneficial to further improve the gram capacity of the composite positive electrode material and the energy density of the positive electrode sheet having the composite positive electrode material.
[0051] On the other hand, the present application also provides a positive electrode sheet, including a current collector and the composite positive electrode material as described above, wherein the composite positive electrode material is located on the surface of the current collector, which can effectively improve the high temperature resistance and energy density of the positive electrode sheet, and achieve a synergistic improvement in reversible gram capacity, energy density, room temperature cycle performance, high temperature cycle performance and life.
[0052] On the other hand, the present application also provides a secondary battery, including the composite positive electrode material as described above, or including the positive electrode sheet as described above, which can effectively improve the high temperature resistance and energy density of the secondary battery, and achieve a synergistic improvement in reversible gram capacity, energy density, room temperature cycle performance, high temperature cycle performance and life.
[0053] On the other hand, the present application also provides an electronic device, comprising the secondary battery as described above.
[0054] On the other hand, the present application also provides a method for preparing a composite positive electrode material, comprising: S1, dispersing a composite sodium iron sulfate material and a carbon-coated sodium iron phosphate pyrophosphate material in a solvent according to a first mass ratio, and mixing them to form a composite slurry; S2, coating the composite slurry on the surface of the current collector and drying it to form the composite positive electrode material on the surface of the current collector.
[0055] Among them, the first mass ratio is 1:1 to 5:1, which is equal to the mass ratio between the composite sodium ferric sulfate material and the carbon-coated sodium ferric phosphate pyrophosphate material in the composite positive electrode material; the solvent can be N-methylpyrrolidone, which has good solubility and dispersibility for the composite sodium ferric sulfate material and the carbon-coated sodium ferric phosphate pyrophosphate material, which is beneficial to the subsequent coating of the carbon-coated sodium ferric phosphate pyrophosphate material on the composite sodium ferric sulfate material, thereby improving the high temperature resistance and gram capacity of the composite positive electrode material.
[0056] In some exemplary embodiments, in step S1, the conductive agent and the binder are also dispersed together in the solvent, wherein the mass proportion of the conductive agent in the composite sodium ferric sulfate material, the carbon-coated sodium ferric phosphate pyrophosphate material, the conductive agent and the binder is 0.1% to 10%, and the mass proportion of the binder in the composite sodium ferric sulfate material, the carbon-coated sodium ferric phosphate pyrophosphate material, the conductive agent and the binder is 0.1% to 10%, so as to improve the processability of the composite slurry and improve the film forming accuracy and film forming stability of the composite positive electrode material.
[0057] In step S2, the current collector can be a carbon-coated aluminum foil. After the composite slurry is coated on the surface of the current collector, it is dried under vacuum conditions at 120°C for 12 hours to allow the composite slurry to dry and solidify into a film, forming a composite positive electrode material on the current collector. The composite positive electrode material is a positive electrode film layer, and the positive electrode film layer and the current collector together form a positive electrode sheet. The positive electrode sheet and the secondary battery having the positive electrode sheet can have higher energy density and better high-temperature cycle performance.
[0058] The following describes the embodiments of the present application in combination with the above technical solutions.
[0059] Example 1 The composite positive electrode material and the secondary battery in this embodiment are prepared by the following steps: 1. Preparation of positive electrode: 45g of carbon-coated sodium iron pyrophosphate material (Na4Fe3(PO4)2P2O7@C) and carbon nanotube composite sodium iron sulfate material (Na x Fe(SO4) y / CNT-5%) 45g, Super-p conductive agent 2g and polyvinylidene fluoride binder 4g were dispersed in N-methylpyrrolidone solvent, mixed evenly and coated on carbon-coated aluminum foil, and dried under vacuum at 120℃ for 12h to obtain a positive electrode sheet with a surface density of 16.6mg / cm 2 ; Among them, the mass ratio of the carbon-coated sodium iron phosphate pyrophosphate material and the carbon nanotube composite sodium iron sulfate material is 1:1, the total surface area of sodium iron sulfate in the composite sodium iron sulfate material is 19.63% of the total surface area of the carbon-coated sodium iron phosphate pyrophosphate material, the D10 of the carbon-coated sodium iron phosphate pyrophosphate material is 0.35μm, D50 is 1.2μm, Dmax is 2.5μm, and the specific surface area is 15m 2 / g; the D10 of the carbon nanotube composite sodium iron sulfate material is 1.8μm, D50 is 4.6μm, and Dmax is 13.9μm, of which the specific surface area of sodium iron sulfate is 3.1m 2 / g.
[0060] 2. Preparation of negative electrode sheet: According to the mass ratio of 95:1.5:2:1.5, 95g of hard carbon negative electrode material, 1.5g of Super-p conductive agent, 2g of styrene-butadiene rubber binder and 1.5g of carboxymethyl cellulose binder were dispersed in pure water, mixed evenly and coated on aluminum foil, and dried at 120°C under vacuum for 12h to obtain a negative electrode sheet with a surface density of 5.6mg / cm 2 .
[0061] 3. Pole sheet die cutting: First, roll the positive electrode sheet according to the surface density to a compaction density of 2g / cm 3 The thickness of the negative electrode sheet is rolled according to the surface density to a compaction density of 1.0g / cm 3 The thickness is 43mm; the positive electrode sheet is die-cut into a square positive electrode sheet with a width of 43mm, a length of 56m, a tab length of 8mm and a width of 6mm; the negative electrode sheet is die-cut into a square negative electrode sheet with a width of 45mm, a length of 58m, a tab length of 7mm and a width of 6mm.
[0062] 4. Preparation of the whole battery: Weld the positive and negative electrode sheets with the electrode ears with an electric welder, then stack them in the order of positive electrode sheet, diaphragm and negative electrode sheet, fix them, and put them together in a semi-sealed aluminum-plastic film. After completing the top and side sealing, transfer them to 85°C and dry them under vacuum conditions for 48 hours; add an electrolyte with sodium hexafluorophosphate as the solute, ethylene carbonate and propylene carbonate in a volume ratio of 1:1 as the solvent, and a solute concentration of 1 mol / L to the battery cell after drying, and obtain a sodium ion soft-pack battery after vacuum packaging.
[0063] 5. Preparation of button cells: In addition, after steps 1-3, the positive electrode sheet, glass fiber separator and metal sodium sheet can be prepared into button cells in order, and 20 μL of electrolyte is injected to obtain a button cell; wherein the solvent of the electrolyte is PC, and the solute is 1 mol / L sodium perchlorate.
[0064] Example 2 The difference between this embodiment and embodiment 1 is that, in the process of preparing the positive electrode sheet, the mass of the carbon-coated sodium iron phosphate pyrophosphate material is 30g, and the mass of the carbon nanotube composite sodium iron sulfate material is 60g, that is, the mass ratio of the carbon-coated sodium iron phosphate pyrophosphate material to the carbon nanotube composite sodium iron sulfate material is 1:2, and the total surface area of sodium iron sulfate in the composite sodium iron sulfate material is 39.27% of the total surface area of the carbon-coated sodium iron phosphate pyrophosphate material; the rest is the same as embodiment 1.
[0065] Example 3 The difference between this embodiment and embodiment 1 is that in the process of preparing the positive electrode sheet, the carbon-coated sodium iron phosphate pyrophosphate material has a D10 of 0.45 μm, a D50 of 1.23 μm, a Dmax of 2.8 μm, and a specific surface area of 14.3 m 2 / g; the total surface area of sodium ferric sulfate in the composite sodium ferric sulfate material is 20.59% of the total surface area of the carbon-coated sodium ferric phosphate pyrophosphate material; the rest is the same as Example 1.
[0066] Example 4 The difference between this embodiment and embodiment 1 is that in the process of preparing the positive electrode sheet, the D10 of the composite sodium iron sulfate material is 1.8 μm, the D50 is 4.6 μm, the Dmax is 10.2 μm, and the specific surface area is 12.1 m 2 / g; the total surface area of sodium ferric sulfate in the composite sodium ferric sulfate material is 24.34% of the total surface area of the carbon-coated sodium ferric phosphate pyrophosphate material; the rest is the same as Example 1.
[0067] Example 5 The difference between this embodiment and embodiment 1 is that in the process of preparing the positive electrode sheet, the specific surface area of sodium iron sulfate is 4.8 m 2 / g, the specific surface area of the carbon-coated sodium iron phosphate pyrophosphate material is 16.1m 2 / g; the total surface area of sodium ferric sulfate in the composite sodium ferric sulfate material is 28.32% of the total surface area of the carbon-coated sodium ferric phosphate pyrophosphate material; the rest is the same as Example 1.
[0068] Example 6 The difference between this embodiment and embodiment 1 is that, in the process of preparing the positive electrode sheet, the total surface area of sodium ferric sulfate in the composite sodium ferric sulfate material is 33% of the total surface area of the carbon-coated sodium ferric phosphate pyrophosphate material; the rest is the same as embodiment 1.
[0069] Example 7 The difference between this embodiment and embodiment 1 is that, in the process of preparing the positive electrode sheet, the mass percentage of carbon nanotubes in the composite sodium iron sulfate material is 3.5%; the rest is the same as embodiment 1.
[0070] Example 8 The difference between this embodiment and embodiment 1 is that, in the process of preparing the positive electrode sheet, the mass percentage of the second carbon material in the carbon-coated sodium iron phosphate pyrophosphate material is 3%; the rest is the same as embodiment 1.
[0071] Comparative Example 1 The difference between this comparative example and Example 1 is that, in the process of preparing the positive electrode sheet, the mass of the carbon-coated sodium iron phosphate pyrophosphate material is 90g, and the mass of the carbon nanotube composite sodium iron sulfate material is 0g, that is, a simple carbon-coated sodium iron phosphate pyrophosphate material is used as the positive electrode film layer; the rest is the same as Example 1.
[0072] Comparative Example 2 The difference between this comparative example and Example 1 is that, in the process of preparing the positive electrode sheet, the mass of the carbon-coated sodium iron pyrophosphate material is 0 g, and the mass of the carbon nanotube composite sodium iron sulfate material is 90 g, that is, a pure carbon nanotube composite sodium iron sulfate material is used as the positive electrode film layer; the rest is the same as Example 1.
[0073] Comparative Example 3 The difference between this comparative example and Example 1 is that in the process of preparing the positive electrode sheet, the carbon-coated sodium iron phosphate pyrophosphate material has a D10 of 3.2 μm, a D50 of 7.5 μm, a Dmax of 15.8 μm, and a specific surface area of 5.6 m 2 / g,; the total surface area of sodium ferric sulfate in the composite sodium ferric sulfate material is 52.59% of the total surface area of the carbon-coated sodium ferric phosphate pyrophosphate material; the rest is the same as Example 1.
[0074] Comparative Example 4 The difference between this comparative example and Example 1 is that in the process of preparing the positive electrode sheet, the carbon-coated sodium iron phosphate pyrophosphate material has a D10 of 0.5 μm, a D50 of 0.95 μm, a Dmax of 2.2 μm, and a specific surface area of 25 m 2 / g, the total surface area of sodium ferric sulfate in the composite sodium ferric sulfate material is 11.78% of the total surface area of the carbon-coated sodium ferric phosphate pyrophosphate material; the rest is the same as Example 1.
[0075] Table 1 Full battery test data of the composite positive electrode materials of the embodiment and the positive electrode materials of the comparative example
[0076] The battery cells with the composite positive electrode material in the embodiment and the battery cells with the positive electrode material in the comparative example were subjected to full battery performance tests. The test data are shown in Table 1 above. It can be seen that, compared with the battery using only the carbon-coated sodium iron phosphate pyrophosphate material in comparative example 1 and the battery using only the composite sodium iron sulfate in comparative example 2, the composite positive electrode materials in embodiments 1-8 are applied to the secondary battery, which can make the reversible gram capacity, battery energy density, 1C / 1C room temperature cycle 2000 cycle capacity retention rate and 1C / 1C high temperature 55°C cycle 800 cycle capacity retention rate of the battery cell synergistically improved to varying degrees; in addition, the carbon-coated sodium iron phosphate pyrophosphate material in comparative example 3 The particle size is too large, and the ratio of the total surface area of the composite sodium ferric sulfate material to the total surface area of the carbon-coated sodium ferric phosphate pyrophosphate material in Comparative Example 4 is too small, making it difficult to form a good coating on the surface of the composite sodium ferric sulfate material, resulting in poor overall performance, and even a lower capacity retention rate than that of the battery in Comparative Example 1 that only uses carbon-coated sodium ferric phosphate pyrophosphate material. It is difficult to achieve a balance between reversible gram capacity, energy density and cycle performance. That is, only within the particle size range and surface area range provided in the present application can the carbon-coated sodium ferric phosphate pyrophosphate material be effectively coated on the composite sodium ferric sulfate material, thereby achieving a synergistic improvement in reversible gram capacity, energy density, room temperature cycle performance and high temperature cycle performance.
[0077] It should be noted that the various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0078] What is described above are only some embodiments of the present application and are not intended to limit the present application. Those skilled in the art should understand that the present application may undergo various changes and improvements, and any modifications, equivalent substitutions and improvements made in accordance with the present application shall fall within the scope of protection required by the present application.
Claims
1. A composite positive electrode material, characterized in that: It includes a composite sodium iron sulfate material and a carbon-coated sodium iron phosphate pyrophosphate material, wherein the composite sodium iron sulfate material includes a first carbon material and sodium iron sulfate, and the first carbon material and the sodium iron sulfate are blended; the carbon-coated sodium iron phosphate pyrophosphate material includes a second carbon material and sodium iron phosphate pyrophosphate, and the second carbon material coats the sodium iron phosphate pyrophosphate; the carbon-coated sodium iron phosphate pyrophosphate material coats the composite sodium iron sulfate material.
2. The composite positive electrode material according to claim 1, characterized in that The mass of each component in the composite positive electrode material satisfies at least one of the following characteristics: The mass ratio between the composite sodium iron sulfate material and the carbon-coated sodium iron phosphate pyrophosphate material is 1:1 to 5:1; The mass percentage of the composite sodium iron sulfate material in the composite positive electrode material is 40% to 95%; The mass percentage of the carbon-coated sodium iron phosphate pyrophosphate material in the composite positive electrode material is 5% to 60%.
3. The composite positive electrode material according to claim 1, characterized in that: The molecular formula of sodium ferric sulfate in the composite sodium ferric sulfate material is Na m Fe(SO4) n , where m+2=2n, 0.8≤m≤3.2, 1.3≤n≤2.
7.
4. The composite positive electrode material according to claim 1, characterized in that The particle size of the composite positive electrode material satisfies at least one of the following characteristics: The particle size of the composite sodium iron sulfate material is greater than the particle size of the carbon-coated sodium iron phosphate pyrophosphate material; The median particle size of the composite sodium iron sulfate material is smaller than the first preset particle size, and the first preset particle size is 3 μm to 7 μm; The median particle size of the carbon-coated sodium iron phosphate pyrophosphate material is smaller than the second preset particle size, and the second preset particle size is 1 μm to 2.5 μm.
5. The composite positive electrode material according to claim 1, characterized in that: The surface area of the composite positive electrode material satisfies at least one of the following characteristics: The total surface area of the sodium iron sulfate in the composite sodium iron sulfate material is 15% to 50% of the total surface area of the carbon-coated sodium iron phosphate pyrophosphate material; The specific surface area of sodium iron sulfate in the composite sodium iron sulfate material is 2m 2 / g~5m 2 / g; The specific surface area of the first carbon material in the composite sodium iron sulfate material is 50 2 / g~350m 2 / g; the specific surface area of the carbon-coated sodium iron phosphate pyrophosphate material is 12m 2 / g~25m 2 / g.
6. The composite positive electrode material according to any one of claims 1 to 5, characterized in that: The first carbon material and the second carbon material satisfy at least one of the following characteristics: The mass percentage of the first carbon material in the composite sodium iron sulfate material is 2% to 10%; the mass percentage of the second carbon material in the carbon-coated sodium iron phosphate pyrophosphate material is 1% to 5%.
7. The composite positive electrode material according to any one of claims 1 to 5, characterized in that: The composite positive electrode material further includes at least one of a conductive agent and a binder, and the composite positive electrode material satisfies at least one of the following characteristics: The conductive agent includes at least one of conductive carbon black, acetylene black, graphite, graphene, carbon nanotubes and carbon nanofibers; The mass percentage of the conductive agent in the composite positive electrode material is 0.1% to 10%; the binder includes at least one of polyvinylidene fluoride, modified polyvinylidene fluoride, polyvinylidene chloride, modified polyvinylidene chloride, polyvinylidene fluoride copolymer, polyvinylidene chloride copolymer, polymethyl methacrylate and styrene-butadiene rubber; The mass percentage of the binder in the composite positive electrode material is 0.1% to 10%.
8. The composite positive electrode material according to any one of claims 1 to 5, characterized in that: The compaction density of the composite positive electrode material is 1.9 g / cm 3 ~2.4g / cm 3 .
9. A positive electrode sheet, characterized in that: It comprises a current collector and the composite positive electrode material according to any one of claims 1 to 8, wherein the composite positive electrode material is located on the surface of the current collector.
10. A secondary battery, characterized in that: It comprises the composite positive electrode material as described in any one of claims 1 to 8, or comprises the positive electrode sheet as described in claim 9.
Citation Information
Cited By
Low-alkalinity sodium ferric pyrophosphate positive electrode material and preparation method thereof
CN120809789A
Sodium ferric sulfate composite sodium ion positive electrode material, preparation method thereof and battery
CN120878796A
Sodium sulfate iron composite sodium ion positive electrode material and preparation method and battery thereof
CN120878796B
